Organic photoelectric detector based on metal-induced adsorption enhanced interface and preparation
By adding a metal-induced layer between the active layer of the organic photodetector and the interface modification layer, the problem of insufficient specific detection rate and stability in the prior art is solved, and a higher specific detection rate and stability is achieved, especially in terms of near-infrared response.
Patent Information
- Application Number
- CN202411723530.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-25
AI Technical Summary
Existing organic photodetectors have shortcomings in specific detection rate and stability, limiting their performance in large-scale applications.
By adding a metal-induced layer between the active layer and the interface modification layer, the dark current inside the device is reduced, and optical resonant cavity is formed in concert with other structural layers, the thickness of the active layer is regulated to improve response efficiency.
It effectively reduces the dark current, improves the specific detection rate and stability, and shows significant improvements in the near-infrared response band.
Smart Images

Figure CN119698166A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of organic photoelectric detection, and in particular to an organic photoelectric detector based on a metal-induced adsorption enhanced interface (barrier layer) and its preparation. Background Art
[0002] Organic photodetectors have attracted widespread attention due to their unique advantages such as light weight, high flexibility and adjustable band gap. After years of research, their performance has been significantly improved, and some indicators are comparable to those of inorganic photodetectors. Especially in the field of near-infrared detection, they have shown important application value in night vision imaging, optical communications and biometrics. However, current organic photodetectors still have shortcomings in terms of specific detection rate and stability, which limits their performance in large-scale applications.
[0003] As a composite device composed of multiple layers of materials, the interface layer of organic photodetectors plays a vital role in thin film devices. The interface layer not only plays an important role in connecting different functional layers, but also shows its unique advantages in the selective collection and suppression of carriers. Therefore, by selecting specific materials, on the one hand, the transmission of electron or hole carriers is effectively promoted, while the movement of another carrier is suppressed, the dark current is significantly reduced, and the specific detection rate is improved. On the other hand, the corrosion of the active layer to the interface layer is reduced through metal-induced adsorption enhancement, thereby improving the stability of the device. Finally, by using the metal-induced layer and the upper metal electrode to form an optical resonant cavity, the thickness of the active layer is adjusted to achieve the effect of resonant enhancement of the near-infrared photon response, further improving the specific detection rate of the device in the near-infrared response band. By this method, an organic photodetector with high specific detection rate and high stability is obtained, which has far-reaching significance for the application of organic photodetectors. Summary of the invention
[0004] The purpose of the present invention is to overcome the above-mentioned shortcomings and deficiencies of the prior art and to provide an organic photodetector and preparation based on metal-induced adsorption enhanced interface.
[0005] The present invention effectively reduces the dark current inside the device by adding a metal induction layer between the active layer and the interface modification layer. In addition, the metal induction layer also cooperates with other structural layers to form an optical resonant cavity, so that the device response peak is red-shifted, further improving the specific detection rate of the photoelectric detection device, while limiting the corrosion of the active layer on the interface layer, improving the stability of the device, and having important reference significance for reducing the dark current of organic photoelectric detection devices and improving their stability.
[0006] The present invention is achieved through the following technical solutions: An organic photodetector based on metal-induced adsorption enhanced interface; The structure of the organic photodetector includes, from bottom to top, a cathode 1, a cathode interface modification layer 2, a metal induction layer 3, an organic photoactive layer 4, an anode interface modification layer 5, and an anode 6.
[0007] Furthermore, the cathode is indium tin oxide glass (ITO), which is a transparent substrate material with good conductivity.
[0008] Furthermore, the cathode interface modification layer is PFN-Br, ZnO, PDIN, PDINN, PDINO, PNDIT-F3N, PEIE, TiO2, ZnO, LiF, etc., which is spin-coated on the ITO surface to form a film with a thickness of 10~15 nm.
[0009] Preferably, the cathode interface modification layer is PFN-Br with a thickness of 10 nm.
[0010] Furthermore, the metal induction layer is a metal with good conductivity such as Ag, Au, Cu, etc., which is evaporated on the surface of the cathode interface modification layer. The thickness of the metal induction layer is 0.5~10 nm.
[0011] Preferably, the metal induction layer is Au, and the optimal thickness is 1 nm.
[0012] Furthermore, the organic photoactive layer mainly absorbs photons to generate excitons, which dissociate at the interface to generate carriers that enter the corresponding transport layer and are finally collected by the electrode to generate photocurrent. The organic photoactive layer is specifically a bulk heterojunction structure made of a mixture of donor material and acceptor material.
[0013] Furthermore, the donor material is an organic conjugated small molecule, polymer or oligomer material, including: one or more of PTB7 (PCE9), PTB7-Th (PCE10), PBDB-T (PCE12), PBDB-T-2F (PM6), PBDB-T-2Cl (PM7), and D18.
[0014] Furthermore, the receptor material is fullerene and its derivatives, organic conjugated small molecules, polymer or oligomer materials, including: BTP-4F (Y6), Y6-BO, BTP-4Cl (Y7), Y7-BO, L8-BO, BTP-eC7, BTP-eC9, ITIC, ITIC-Th, IEICO, IEICO-4F, IEICO-4Cl, COTIC-4F, COTIC-4Cl and the like.
[0015] Preferably, the active layer is made of PM6:Y6, and the optimal thickness is 230 nm.
[0016] Furthermore, the anode interface modification layer is a metal oxide such as vanadium oxide (VOx), nickel oxide (NiOx), molybdenum oxide (MoOx), etc., and has a thickness of 10-15 nm.
[0017] Preferably, the anode interface modification layer is molybdenum oxide MoO3, and the optimal thickness is 10 nm.
[0018] Furthermore, the anode is one or more of highly conductive and highly reflective metals such as Ag, Al, Au, Cu, or materials with similar functions, and is deposited on the anode modification layer by thermal evaporation with a thickness of 80-120 nm.
[0019] Preferably, the anode is metal Al with a thickness of 100 nm.
[0020] The present invention provides a method for preparing an organic photodetection device based on an interface barrier layer enhanced by metal induced adsorption, comprising the following steps: Step 1: Treat the cathode substrate material: ultrasonically clean the ITO glass substrate with secondary recycled isopropyl alcohol, detergent water, ultrapure water (3 to 4 times), and clean isopropyl alcohol for 15 to 20 minutes. After cleaning, place it in a drying oven at 60 to 70 °C for drying.
[0021] Step 2, deposition of cathode interface modification layer: the dried ITO substrate is placed under a vacuum of less than 100 Pa for 3-4 minutes of plasma surface treatment. The cathode interface modification material solution prepared according to the optimized configuration is filtered through an aqueous polyethersulfone needle filter with a pore diameter of 0.22 μm, and the solution is spin-coated on the ITO substrate with a gel coater. Depending on the type of cathode interface modification material, it is placed on a heating table in a fume hood environment or a glove box environment for reaction or annealing.
[0022] Step 3: Deposition of metal induction layer: The ITO substrate with the cathode interface modification layer spin-coated is moved into the evaporation system. -4 The metal layer is evaporated at a pressure of Pa.
[0023] Step 4, deposition of the photoactive layer: The photoactive layer adopts a bulk heterojunction structure, the donor and the acceptor are weighed according to the optimized mass ratio, dissolved together in the optimized organic solvent, and the active layer is processed by spin coating using a coating machine. After the active layer is formed into a film, post-treatment is performed, such as thermal annealing, removal of high boiling point additives, etc. The process conditions when the donor and the acceptor adopt the following system are as follows: PM 6:Y6 system: The donor-acceptor mass ratio is 1:1.2, the processing solvent is chlorobenzene (CB) or chloroform (CF), and no thermal annealing is performed.
[0024] Step 5: Deposition of anode interface modification layer and anode top electrode: thermal evaporation method was used on 1×10 -4 Pa to 4×10 -4 Pa, metal oxide is evaporated as the anode interface modification layer, and then metal is evaporated as the anode top electrode.
[0025] Compared with the prior art, the present invention has the following advantages and effects: (1) The present invention effectively avoids the destruction of the active layer during the spin coating process by adding a metal induction layer between the organic photoactive layer and the cathode interface modification layer, and also effectively solves the problem of instability of water-alcohol soluble interface materials such as PFN-Br in organic optoelectronic devices.
[0026] (2) The organic photodetection device based on the metal induced interface barrier layer described in the present invention is prepared by solution processing and evaporation, and there is no problem of lattice mismatch in processes such as lattice growth and vapor deposition. The metal induced layer does not require high-temperature heating, and the preparation method is simple and easy to operate, which is feasible and simple to operate.
[0027] (3) The organic photoactive layer of the organic photodetector device based on the metal-induced interface barrier described in the present invention adopts a bulk heterojunction structure, and the thickness of the active layer is small, so the detector has the advantages of high response speed and high responsivity.
[0028] (4) The organic photodetector device based on the metal-induced interface barrier described in the present invention forms a hole injection barrier between the ITO / cathode modification interface layer and the organic photodetector layer by selecting a suitable metal as the metal-induced layer, thereby preventing the reverse injection of dark holes, further reducing the dark current of the device, and improving the specific detection rate of the device, reaching ~10 at a bias voltage of -0.1 V. 13 Jones.
[0029] (5) The metal induced layer of the organic photodetector device based on the metal induced interface barrier layer described in the present invention cooperates with other structural layers to form an optical resonant cavity. By adjusting the thickness of the active layer, the response of the device in the near infrared can be resonantly enhanced, so that the overall response peak is red-shifted. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is a device structure diagram of the metal-induced interface organic photodetector of the present invention; Figure 2 is a relationship diagram between current density and voltage of the organic photodetector devices prepared in Example 1 of the present invention and Comparative Examples 1 and 2 under dark conditions; Figure 3 Graphs showing the specific detection rates of the organic photodetection devices prepared in Example 1 of the present invention and Comparative Examples 1 and 2 under illumination conditions; Figure 4 It is a graph of external quantum efficiency of organic photodetection devices prepared in Example 1 of the present invention and Comparative Examples 1 and 2 under illumination conditions; Figure 5 This is the movement of carriers inside the metal-induced interface organic photodetector of the present invention.
[0031] Figure 6 The figure shows the responsiveness of the organic photodetector devices prepared in Examples 2 and 3 of the present invention under illumination conditions.
[0032] Figure 7 The figure shows the relationship between the current density and the voltage of the organic photodetection devices prepared in Examples 2 and 3 of the present invention under dark conditions.
[0033] Figure 8 The specific detection rate of the organic photodetection devices prepared in Example 2 and Example 3 of the present invention under illumination conditions. DETAILED DESCRIPTION
[0034] The present invention will be further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0035] Example 1 Combination Figure 1 As shown, an organic photodetection device based on an interface barrier layer with metal-induced adsorption enhancement, the device structure of which includes a cathode 1, a cathode interface modification layer 2, a metal-induced layer 3, an organic photoactive layer 4, an anode interface modification layer 5 and an anode 6 in sequence.
[0036] The cathode 1 is indium tin oxide glass (ITO); the cathode interface modification layer 2 is PFN-Br, with a spin coating thickness of 10 nm; the metal induction layer 3 is Au, with a thickness of 1 nm; the organic photoactive layer 4 is a blend of donor material PBDB-T-2F (PM6) and acceptor material BTP-4F (Y6), and the active layer film thickness is 230 nm; the anode interface modification layer 5 is molybdenum oxide (MoOx), with a film thickness of 10 nm; the anode is aluminum, with a film thickness of 100 nm.
[0037] 1. Treatment of cathode substrate materials: Cleaning of ITO substrate: Ultrasonic clean the ITO glass substrate with secondary recovered isopropyl alcohol, detergent water, ultrapure water (3 to 4 times), and clean isopropyl alcohol for 15 to 20 minutes. After cleaning, place it in a drying oven at 60 to 70°C for drying.
[0038] 2. Deposition of cathode interface modification layer: Place the dried ITO substrate under a vacuum of less than 100 Pa for 3-4 minutes of plasma surface treatment. Dissolve PFN-Br in methanol to make a 0.5 mg / mL solution, and deposit a PFN-Br film on the ITO glass by spin coating. The spin coating speed is 2000 rpm, and the spin coating time is 30 s.
[0039] 3. Deposition of metal induction layer: When the cabin pressure drops to 4×10 -4 When the pressure is below Pa, the metal Au particles are heated to evaporate, the evaporation rate is 0.2 Å / s, and the evaporation is stopped when the film thickness reaches 1 nm.
[0040] 4. Deposition of photoactive layer: The active layer material is dissolved in a solution, wherein the donor-acceptor mass ratio of the active layer system PM6:Y6 system is 1:1.2, the processing solvent is chloroform (CF), the total concentration is 16 mg / mL, and the active layer is spin-coated on the upper surface of the metal induction layer at a spin coating speed of 2000 rpm and a spin coating time of 30 s.
[0041] 5. Deposition of anode interface modification layer and metal top electrode: After scraping out the ITO electrode, put on the mask and transfer the substrate to the evaporation chamber. When the chamber pressure drops to 4×10 -4 When the pressure is below Pa, MoO3 and metal Al particles are heated successively to make them evaporate. The evaporation rate of the former is 0.2 Å / s, and the evaporation is stopped when the film thickness reaches 10 nm. The evaporation rate of the latter starts at 0.2 Å / s, accelerates to 1-2 Å / s when it reaches 10 nm, and stops when the film thickness reaches 100 nm. The main features of the organic photodetector device in Example 1 are that the cathode interface modification layer is PFN-Br, the average spin coating thickness is 8 nm, and the metal induction layer is Au, the average vapor deposition thickness is 1 nm.
[0042] Comparative Example 1 The preparation methods of Comparative Example 1 and Example 1 are basically the same, except that a metal induction layer Au is first evaporated on the ITO substrate, and then a cathode interface modification layer PFN-Br is spin-coated. The device structure is ITO / PFN-Br / Au / PM6:Y6 / MoO3 / Al.
[0043] 1. Treatment of cathode substrate materials: Cleaning of ITO substrate: Ultrasonic clean the ITO glass substrate with secondary recovered isopropyl alcohol, detergent water, ultrapure water (3 to 4 times), and clean isopropyl alcohol for 15 to 20 minutes. After cleaning, place it in a drying oven at 60 to 70 °C for drying.
[0044] 2. Deposition of metal induction layer: Place the dried ITO substrate in a vacuum of less than 100 Pa for 3-4 minutes of plasma surface treatment. Move the cleaned ITO glass into the evaporation chamber. When the chamber pressure drops to 4×10 -4 When the pressure is below Pa, the metal Au particles are heated to evaporate, the evaporation rate is 0.2 Å / s, and the evaporation is stopped when the film thickness reaches 1 nm.
[0045] 3. Deposition of cathode interface modification layer: PFN-Br was dissolved in methanol to make a 0.5 mg / mL solution, and a layer of PFN-Br film was deposited on the metal induction layer Au by spin coating. The spin coating speed was 2000 rpm and the spin coating time was 30 s.
[0046] 4. Deposition of photoactive layer: The active layer material is dissolved in a solution, wherein the donor-acceptor mass ratio of the active layer system PM6:Y6 system is 1:1.2, the processing solvent is chloroform (CF), the total concentration is 16 mg / mL, and the active layer is spin-coated on the upper surface of the metal induction layer at a spin coating speed of 2000 rpm and a spin coating time of 30 s.
[0047] 5. Deposition of anode interface modification layer and metal top electrode: After scraping out the ITO electrode, put on the mask and transfer the substrate to the evaporation chamber. When the chamber pressure drops to 4×10 -4 When the pressure is below Pa, MoO3 and metal Al particles are heated successively to make them evaporate. The evaporation rate of the former is 0.2 Å / s, and the evaporation is stopped when the film thickness reaches 10 nm. The evaporation rate of the latter starts at 0.2 Å / s, accelerates to 1-2 Å / s when it reaches 10 nm, and stops when the film thickness reaches 100 nm. Comparative Example 2 The preparation methods of Comparative Example 2 and Example 1 and Comparative Example 1 are basically the same, except that the cathode interface modification layer is ZnO, and the device structure does not add a metal induction layer, and its device structure is ITO / ZnO / PM6:Y6 / MoO3 / Al.
[0048] Among them, the cathode 1 is indium tin oxide glass (ITO); the cathode interface modification layer 2 is sol-gel zinc oxide with a film thickness of 30 nm; the organic photoactive layer 4 is a blend of donor material PBDB-T-2F (PM6) and acceptor material BTP-4F (Y6), and the active layer film thickness is 100 nm; the anode interface modification layer 5 is molybdenum oxide (MoOx) with a film thickness of 10 nm; the anode is aluminum with a film thickness of 100 nm.
[0049] 1. Treatment of cathode substrate materials: Cleaning of ITO substrate: Ultrasonic clean the ITO glass substrate with secondary recovered isopropyl alcohol, detergent water, ultrapure water (3 to 4 times), and clean isopropyl alcohol for 15 to 20 minutes. After cleaning, place it in a drying oven at 60 to 70 °C for drying.
[0050] 2. Deposition of cathode interface modification layer: Place the dried ITO substrate under a vacuum of less than 100 Pa for 3-4 minutes of plasma surface treatment. Dissolve 1 g of zinc acetate in 10 mL of ethylene glycol monomethyl ether, add 275 mL of ethanolamine, and place on a 60 °C heating table and stir overnight to obtain a zinc oxide precursor solution. After filtering through an aqueous polyethersulfone needle filter with a pore diameter of 0.22 μm, the zinc oxide precursor solution is spin-coated on the ITO substrate at a speed of 2600 rpm per minute using a sizing machine, and then placed on a 200 °C heating table in a fume hood environment for 1 hour to obtain a 30 nm thick ZnO film, so that the precursor reacts with oxygen in the air to form zinc oxide.
[0051] 4. Deposition of photoactive layer: The active layer material was dissolved in a solution, wherein the donor-acceptor mass ratio of the active layer system PM6:Y6 system was 1:1.2, the processing solvent was chloroform (CF), the total concentration was 16 mg / mL, and the active layer was spin-coated on the surface of the ZnO film at a spin coating speed of 2000 rpm and a spin coating time of 30 s.
[0052] 5. Deposition of anode interface modification layer and metal top electrode: After scraping out the ITO electrode, put on the mask and transfer the substrate to the evaporation chamber. When the chamber pressure drops to 4×10 -4 When the pressure is below Pa, MoO3 and metal Al particles are heated successively to make them evaporate. The evaporation rate of the former is 0.2 Å / s, and the evaporation is stopped when the film thickness reaches 10 nm. The evaporation rate of the latter starts at 0.2 Å / s, accelerates to 1-2 Å / s when it reaches 10 nm, and stops when the film thickness reaches 100 nm. At this point, an organic optoelectronic device based on ZnO cathode interface material has been prepared, and the device structure is ITO / ZnO / PM6:Y6 / MoO3 / Al.
[0053] Figure 2 , Figure 3 , Figure 4The figures are respectively the relationship between current density and voltage under dark conditions, and the specific detectivity and external quantum efficiency under light conditions of the devices of Example 1, Comparative Example 1 and Comparative Example 2. The device structure of Example 1 is ITO / PFN-Br / Au / PM6:Y6 / MoO3 / Al, the device structure of Comparative Example 1 is ITO / Au / PFN-Br / PM6:Y6 / MoO3 / Al, and the device structure of Comparative Example 2 is ITO / ZnO / PM6:Y6 / MoO3 / Al. Figure 5 This is the movement of carriers inside the devices of Example 1 and Comparative Example 1. Figure 2 , Figure 5 It can be seen that in the structure of Example 1, the metal induction layer Au forms a hole injection barrier between the energy levels of PFN-Br and the acceptor Y6, effectively preventing the dark hole carriers from being injected back to form dark current. Therefore, the dark current of the device of Example 1 is lower than that of Comparative Examples 1 and 2 under negative bias conditions, and is only 2.083 nA / cm under -0.1V bias conditions. 2 . Therefore, Figure 3 As shown, the device specific detection rate of Example 1 is significantly higher than that of Comparative Example 1 and Comparative Example 2. It can be seen that the use of metal induction as an interface barrier layer effectively reduces the dark current of the organic photodetection device, thereby improving the performance of the detection device.
[0054] By comparing the device performance of Example 1, Comparative Example 1, and Comparative Example 2 after being placed in a nitrogen glove box for more than 720 hours, the device of Example 1 can still maintain 83.6% of the detection performance for more than one month, which is higher than the performance retention rate of Comparative Example 1 and Comparative Example 2. At the same time, after 24 hours of irradiation with one unit of sunlight, the performance retention rate of Example 1 is also the highest. This shows that the metal induction layer effectively reduces the erosion of the active layer on the cathode interface modification layer, and effectively improves the time stability and light stability of the organic optoelectronic device.
[0055] Table 1 Overview of the time stability and light stability of Example 1 and Comparative Example 1 and Comparative Example 2.
[0056]
[0057] In addition, in Example 1, since the metal induction layer and other structural layers form an optical resonant cavity structure, the optical resonant cavity resonance can be adjusted by adjusting the reflectivity of the anode electrode and the metal induction layer and the thickness of the active layer to enhance the photon response of different wavelengths. Based on the device structure of Example 1, by adjusting the thickness of the active layer, we prepared the devices of Example 2 and Example 3 with active layer thicknesses of about 150nm and 800nm respectively. The parameters of the responsivity, dark current, and specific detection rate are as follows: Figure 6 , 7 , as shown in Figure 8.
[0058] As shown in the figure, by increasing the thickness of the active layer while keeping the thickness of the metal induction layer and the anode electrode unchanged, the peak value of Example 3 in terms of responsivity is red-shifted by 55nm as a whole, and the peak value is improved. Although the responsivity in the visible light band is enhanced due to the increase in the thickness of the active layer to enhance the absorption of visible light, the photons cannot penetrate into the active layer, resulting in a decrease in response. However, since the increase in the thickness of the active layer suppresses the dark current, the overall specific detection rate of the device in Example 3 is still higher than that of the device in Example 2 in all bands, especially in the near-infrared band, the peak value of the specific detection rate is red-shifted, which effectively enhances the near-infrared response capability of the material system.
[0059] The preparation methods of each step described in the above embodiments include any one or more combinations of solution coating, spin coating, screen printing, inkjet printing, spray coating or vacuum thermal evaporation film formation.
[0060] The implementation methods of the present invention are not limited to the above-mentioned embodiments, and any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.
Claims
1. An organic photodetector based on metal-induced adsorption enhanced interface, characterized in that: The structure of the organic photodetector comprises, from bottom to top, a cathode (1), a cathode interface modification layer (2), a metal induction layer (3), an organic photoactive layer (4), an anode interface modification layer (5), and an anode (6).
2. The organic photodetector based on metal-induced adsorption enhanced interface according to claim 1, characterized in that: The cathode (1) is indium tin oxide glass (ITO).
3. The organic photodetector based on metal-induced adsorption enhanced interface according to claim 1, characterized in that: The cathode interface modification layer (2) is PFN-Br, ZnO, PDIN, PDINN, PDINO, PNDIT-F3N, PEIE, TiO2, ZnO and / or LiF, which is spin-coated on the ITO surface to form a film with a thickness of 10-15 nm.
4. The organic photodetector based on metal-induced adsorption enhanced interface according to claim 1, characterized in that: The metal induction layer (3) is Ag, Au and / or Cu, and is evaporated on the surface of the anode interface modification layer (5); the thickness of the metal induction layer (3) is 0.5-10 nm.
5. The organic photodetector based on metal-induced adsorption enhanced interface according to claim 1, characterized in that: The organic photoactive layer (4) is a bulk heterojunction structure made by mixing a donor material and an acceptor material; The donor material includes one or more of PTB7 (PCE9), PTB7-Th (PCE10), PBDB-T (PCE12), PBDB-T-2F (PM6), PBDB-T-2Cl (PM7), and D18; The acceptor material includes one or more of BTP-4F (Y6), Y6-BO, BTP-4Cl (Y7), Y7-BO, L8-BO, BTP-eC7, BTP-eC9, ITIC, ITIC-Th, IEICO, IEICO-4F, IEICO-4Cl, COTIC-4F, and COTIC-4Cl.
6. The organic photodetector based on metal-induced adsorption enhanced interface according to claim 1, characterized in that: The anode interface modification layer is vanadium oxide (VOx), nickel oxide (NiOx) and / or molybdenum oxide (MoOx), and has a thickness of 10-15 nm.
7. The organic photodetector based on metal-induced adsorption enhanced interface according to claim 1, characterized in that: The anode (6) is one or more of Ag, Al, Au and Cu, and has a thickness of 80-120 nm.
8. The method for preparing an organic photodetector based on metal-induced adsorption enhanced interface according to any one of claims 1 to 7, characterized in that: The steps include: (1) Processing of cathode substrate materials: The ITO glass substrate was ultrasonically cleaned for 15-20 min using secondary recycled isopropyl alcohol, detergent water, ultrapure water, and clean isopropyl alcohol in sequence. After cleaning, it was placed in a drying oven at 60-70 °C for drying. (2) Deposition of cathode interface modification layer (2): The dried ITO substrate is placed under a vacuum degree of less than 100 Pa for 3 to 4 minutes of plasma surface treatment; the cathode interface modification material solution configured according to the optimization is filtered through an aqueous polyethersulfone needle filter with a pore diameter of 0.22 μm, and the solution is spin-coated on the ITO substrate with a gel coater, and is placed on a heating table for reaction or annealing in a fume hood environment or a glove box environment according to the type of cathode interface modification material; (3) Deposition of metal induction layer: The ITO substrate with the cathode interface modification layer was moved into the evaporation system at 4×10 -4 Pa pressure under the vapor deposition of metal layer; (4) Deposition of organic photoactive layer: The organic photoactive layer (4) adopts a bulk heterojunction structure, the donor and the acceptor are dissolved in an optimized organic solvent, and the active layer is processed by spin coating using a coating machine, and the active layer is post-processed after film formation; (5) Deposition of anode interface modification layer and anode top electrode: The thermal evaporation method was used to deposit 1×10 -4 Pa to 4×10 -4 Pa, metal oxide is evaporated as the anode interface modification layer, and then metal is evaporated as the anode top electrode.
9. The method for preparing an organic photodetector based on metal-induced adsorption enhanced interface according to claim 8, characterized in that: In step (3): The preparation method of the metal induction layer is as follows: the metal is prepared as the metal induction layer by thermal evaporation or nanoparticle solution deposition, and then metal oxide MoO3 is evaporated on the metal induction layer as the anode interface modification layer and Al or Ag is evaporated as the anode top electrode.
10. The method for preparing an organic photodetector based on metal-induced adsorption enhanced interface according to claim 8, characterized in that: In step (4): When the donor and acceptor adopt PM6:Y6 system: the donor-acceptor mass ratio is 1:1.2, the processing solvent is chlorobenzene (CB) or chloroform (CF), and no thermal annealing is performed.
Citation Information
Patent Citations
Organic photoelectric detector based on optical microcavity effect and preparation method thereof
CN111883666A
Organic photoelectric device based on metal-induced organic interface layer and preparation method
CN114784193A
Organic optical detector with ultralow dark current and high specific detection rate and preparation
CN115623794A
Composite electrode organic photoelectric detector with high near-infrared response and preparation method thereof
CN116437676A
Organic microcavity photodetectors with narrow and tunable spectral response
US20200227642A1